Clinical and epidemiological data on epilepsy in the Republic of Bashkortostan - L. B. Novikova; A. P. Akopian; K. M. Sharapova (Эпилепсия и пароксизмальные состояния, 2019)
Objective – to conduct a retrospective study on the prevalence of epilepsy and the use of antiepileptic drugs (AED) in the adult population of the Republic of Bashkortostan (RB) in 2013-2017.Materials and methods. The study was carried out by analyzing the data of annual reports by the neurology services of outpatient and inpatient medical institutions in cities and regions of the Republic of Bashkortostan. In addition, we used the results of clinical examinations of patients with confirmed epilepsy and the data from the Medical Information and Analytical Center (MIAC).Results. The prevalence of epilepsy in the RB in 2013-2017 was 291.7-325.8 cases per 100 000 population; the incidence of epilepsy was higher in the central and eastern regions of the Republic. The average age of these patients ranged from 30.5±1.3 years to 41.8±0.2 years. The men/ women ratio was 1.1/1.0. The incidence rate of symptomatic epilepsy ranged from 82.6% to 46.5%. Of AED, carbamazepine was used most often (47.4% of patients) followed by valproic acid (up to 32.9%). AED of the new generation (perampanel) were rarely used (2.4%).Discussion. According to the data for 2016, the prevalence of epilepsy (per 100 000 population) in the RB exceeded the average figure for Russia as a whole: 323.4 in the Republic of Bashkortostan and 255.4 in the Russian Federation. Patients of young age (up to 40 years old) prevailed; among those, men took some lead. According to the literature, the gender difference in the prevalence of epilepsy remains minimal. As for the etiology, symptomatic epilepsy was the predominant form, with an increased presence of cryptogenic and idiopathic epilepsy in 2016-17. The “basic” AED were largely used for the treatment. Conclusion. Studying the clinical and epidemiological characteristics of epilepsy is important for the systemic organization of specialized medical care and the improvement of life quality in patients with epilepsy.